Aberrant Cholesterol Metabolism and Wnt/β‐Catenin Signaling Coalesce via Frizzled5 in Supporting Cancer Growth. Issue 28 (17th August 2022) - Zheng, Shaoqin; Lin, Jiahui; Pang, Zhongqiu; Zhang, Hui; Wang, Yinuo; Ma, Lanjing; Zhang, Haijiao; Zhang, Xi; Chen, Maorong; Zhang, Xinjun; Zhao, Chao; Qi, Jun; et al.
Abstract: Frizzled (Fzd) proteins are Wnt receptors and play essential roles in development, homeostasis, and oncogenesis. How Wnt/Fzd signaling is coupled to physiological regulation remains unknown. Cholesterol is reported as a signaling molecule regulating morphogen such as Hedgehog signaling. Despite the elusiveness of the in‐depth mechanism, it is well‐established that pancreatic cancer specially requires abnormal cholesterol metabolism levels for growth. In this study, it is unexpectedly found that among ten Fzds, Fzd5 has a unique capacity to bind cholesterol specifically through its conserved extracellular linker region. Cholesterol‐binding enables Fzd5 palmitoylation, which is indispensable for receptor maturation and trafficking to the plasma membrane. In Wnt‐addicted pancreatic ductal adenocarcinoma (PDAC), cholesterol stimulates tumor growth via Fzd5‐mediated Wnt/ β ‐catenin signaling. A natural oxysterol, 25‐hydroxylsterol competes with cholesterol and inhibits Fzd5 maturation and Wnt signaling, thereby alleviating PDAC growth. This cholesterol‐receptor interaction and ensuing receptor lipidation uncover a novel mechanism by which Fzd5 acts as a cholesterol sensor and pivotal connection coupling lipid metabolism to morphogen signaling. These findings further suggest that cholesterol‐targeting may provide new therapeutic opportunities for treating Wnt‐dependent cancers. Abstract : The mechanism of Frizzled (Fzd) receptor regulation and aberrant cholesterol metabolism in pancreatic cancer are largely unknown. This study reveals that cholesterol specifically binds to Fzd5 and enables Fzd5 maturation to activate Wnt/ β ‐catenin signaling which is required for pancreatic cancer. Therefore, Fzd5 crucially coalesces cholesterol metabolism and Wnt/ β ‐catenin signaling, and oxysterol provides new therapeutic promise in cancer treatment.